Great teaching by design : from intention to implementation in the visible learning classroom - Hattie, John; Bustamante, Vince; Almarode, John; Fisher, Douglas, 1965-; Frey, Nancy, 1959- (Thousand Oaks, California : Corwin Press, 2021)
'In Great Teaching by Design, the authors explore what future and new teachers need to know and should know about teaching in today's classrooms. The role of teacher expectations, teacher credibility, collective efficacy, and developing assessment-capable visible learners will serve as a platform for making an impact in their future schools and classrooms'--
Includes bibliographical references and index.
Keywords: Effective teaching -- United States; Teacher effectiveness -- United States; Teachers -- Training of -- United States; Teachers -- In service training -- United States